Innovative Delivery and Release Systems for Antioxidants and Other Active Substances in the Treatment of Cancer - Zerrin Sezgin-Bayindir; Sonia Losada-Barreiro; Sofía Fernández-Bravo; Carlos Bravo-Díaz (MDPI AG, 2023)
Cancer is one of the major diseases leading to death worldwide, and the fight against the disease is still challenging. Cancer diseases are usually associated with increased oxidative stress and the accumulation of reactive oxygen and nitrogen species as a result of metabolic alterations or signaling aberrations. While numerous antioxidants exhibit potential therapeutic properties, their clinical efficiency against cancer is limited and even unproven. Conventional anticancer antioxidants and drugs have, among others, the great disadvantage of low bioavailability, poor targeting efficiency, and serious side effects, constraining their use in the fight against diseases. Here, we review the rationale for and recent advances in potential delivery systems that could eventually be employed in clinical research on antioxidant therapy in cancer. We also review some of the various strategies aimed at enhancing the solubility of poorly water-soluble active drugs, including engineered delivery systems such as lipid-based, polymeric, and inorganic formulations. The use of cyclodextrins, micro- and nanoemulsions, and thermosensitive smart liposomes as useful systems for the delivery and release of poorly aqueous-soluble drugs, improving their bioactivity and stability, is also addressed. We also provide some details on their formulation processes and their use in a variety of medical applications. Finally, we briefly cover a case study specifically focused on the use of delivery systems to minimize oral cancer and associated dental problems.